2015
DOI: 10.1080/11263504.2014.1000424
|View full text |Cite
|
Sign up to set email alerts
|

Threatened Sardinian vascular flora: A synthesis of 10 years of monitoring activities

Abstract: The in situ conservation activities carried out in the last 10 years on endemic and threatened Sardinian vascular flora were analysed. Monitored species were selected following the policy species (listed in the Habitat Directive) and following the regional responsibility criterion. A monitoring scheme, with three levels of intensity, was applied and economic costs of the monitoring activities were analysed. In the 10-year long field work, 49 taxa corresponding to 50% of policy species and to 22.5% of the Sardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Thus, the high GAP values were consistent with both ESR (Figure 3b) and intensity of the activities (Figure 5(c)). As discussed by Fenu et al (2015) and also confirmed by the GAP analysis for the policy species, the increasing transportation costs represented a further impediment which biased the conservation activities through the easier to reach areas ( Figure 5(d)). …”
Section: Active Conservation Measuresmentioning
confidence: 60%
“…Thus, the high GAP values were consistent with both ESR (Figure 3b) and intensity of the activities (Figure 5(c)). As discussed by Fenu et al (2015) and also confirmed by the GAP analysis for the policy species, the increasing transportation costs represented a further impediment which biased the conservation activities through the easier to reach areas ( Figure 5(d)). …”
Section: Active Conservation Measuresmentioning
confidence: 60%
“…To plan effective conservation measures when needed for plants of conservation interest, basic information about the distribution ranges, ecological requirements, population numbers, population sizes, and, if possible, demographic patterns (i.e., vital rates) is required [ 14 , 15 , 21 , 69 ]. However, omitting the complex studies of population dynamics, plant population monitoring programmes are also particularly scarce because they are time- and resource-consuming and are therefore restricted to a few threatened species [ 11 , 23 , 24 , 70 ]. Thus, the knowledge about the biology, ecology, and conservation status of most plant species remains remarkably poor; this lack of knowledge is even more relevant in the case of plants neglected, recently described, typical or exclusive of dynamic or peculiar habitats, such as ecotones, or in the case of plants restricted to small and scattered populations, growing on microhabitats difficult to access, such as rocky sites [ 14 , 23 , 24 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some plant species, generally narrow endemics, by their nature have very small or scattered populations, often extremely adapted to their environment. Since narrow endemic plants are often reduced to a small contingent of individuals or are frequently threatened, they constitute a pivotal group for conservation [ 6 , 11 , 12 ]. Regardless, to be effective, conservation actions for those species require reliable basic information about the distribution ranges, ecological requirements, population numbers, population sizes, and, if possible, demographic patterns (i.e., vital rates) over a defined period of time [ 3 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Sardinia is not an exception: despite the high level of uniqueness in the vascular flora, until a few years ago not many conservation studies and actions had been carried out on threatened plant species, and the few studies were mainly oriented on extremely narrow endemic and endemic plants. Only in the last years has a trend inversion been registered, with an increasing number of papers and conservation actions detected about the threatened flora, indicating that greater attention is being paid to threatened plants and, in general, to the island’s plant diversity (e.g., [ 21 , 27 ]). Nonetheless, mainly due to limited human and economic resources (e.g., [ 24 , 25 ]), these conservation achievements are not enough to protect Sardinia’s high level of plant diversity, therefore conserving the most threatened wild species in the island is more urgently needed than ever before.…”
Section: Introductionmentioning
confidence: 99%